Atuação da professora de educação especial em uma escola de educação básica - Lana, Larissa Ribeiro Dalla (2019)
This dissertation presents the paths of an investigation built with the Professional Master of Public Policy and Educational Management in the research line Pedagogical Management and Educational Contexts of the Postgraduate Program in Public Policies and Educational Management of the Federal University of Santa Maria. This research is also linked to the studies developed in the Study and Research Group on Special Education and Inclusion (GEPE). The research seeks to understand the daily perception of teachers of an inclusive regular school about the institutionalization of the performance of the Special Education teacher and thus to think about the possibilities of articulation of the work of the Special Education teacher in Basic Education. For this, the research problem that moves me to think is: How is the performance of the teacher of Special Education and Special Education institutionalized in an inclusive regular school? Methodologically the research work was developed from a collection of information together with the teachers and the management team of a Basic Education institution using open questionnaires with questions related to the possibility of: identify the institutionalization of perspectives regarding the student to be attended by the Special Education teacher; identify the difficulties teachers encounter in the teaching and learning process of these students; and to analyze how teachers see the role of the Special Education teacher in this school. Thus, assuming the analysis of the questionnaires answered by the teachers Pejuçara Elementary School, one can identify three analytical units: “Special Education Teachers: How Institutionally Basic Education Teachers Tell about the Presence of the Special Education Teacher”, “Subjects of Special Education by teachers” and “Teachers' performance in relation to inclusion”. The analysis of these units shows the presence of the Special Education teacher in this school context is essential and is recognized for having specific knowledge of the area, for having access to instrumental and technical resources that are put into operation in the school context. Soon the teachers tell of the importance that the teacher of Special Education has in acting in resources room as well as in regular classroom through the possibility of pedagogical articulations. Given this, the product of this dissertation is presented in the form of a draft Resolution for the performance of Special Education and education professionals from the structuring, organization and creation of working conditions for an inclusive school.